The TOPSIS Method Based on an Ergonomics Approach in Public Transportation in Surakarta to Support Local Economic Sustainability - Diansari, Brillian Nur; Agusti, Febrina; Wibowo, Dimas Satria; Ainurrahman, Arifa (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
In Surakarta City, high mobility is shown by 2023 vehicle registration data, where passenger cars and motorcycles made up 95,19% of all vehicles, while public transport units numbered only 354. In 2024, the city’s economy grew by 5,61%, led by the Information and Communication sector. However, transportation did not contribute significantly, even though efficient public transport is crucial for sustainable urban growth. This study aims to recommend suitable public transportation modes for Surakarta that address mobility challenges and support integrates transportation ergonomics focusing on convenient, safety, accessibility and inclusivity into the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to evaluate alternatives. Using a validated and reliable questionnaire distributed through purposive sampling, the study assessed several modes. The TOPSIS results show closeness coefficients of 0,847 for Batik Solo Trans (BST), 0,649 for taxis and motorcycle taxis, 0,593 for feeder minibuses, and 0,152 for pedicabs. BST emerged as the most suitable mode, offering potential to enhance mobility, streamline logistics, and attract investment. The findings highlight the importance of ergonomics-based transport policies that improve user experience and encourage a shift from private to public transportation, strengthening Surakarta’s economic resilience.